Bottom‑up impact on the cecidomyiid leaf galler and its parasitism in a tropical rainforest - Malinga, Geoffrey M.; Valtonen, Anu; Nyeko, Philip; Vesterinen, Eero J.; Roininen, Heikki (Oecologia, 2014)
The relative importance of host-plant resources, natural enemies or their interactions in controlling the population of galling insects and their parasitism is poorly known for tropical gallers. In this study, we assessed the impacts of plant quality and density of host trees in regulating the densities of a galler species, the cecidomyiid leaf galler (Cecidomyiini sp. 1EJV) and its parasitoids and inquilines on Neoboutonia macrocalyx trees in Uganda. We manipulated the nutritional quality (or vigour) and the resource concentration with four levels each of fertilization and the group size of host tree. We then recorded the effects of these treatments on the growth rate and total leaf area of host plants, the density of gallers and their mortality by parasitoids and inquilines. Higher levels of fertilization and host density resulted in significantly higher total leaf area than did ambient nutrient levels, and lowest tree densities, respectively. Fertilization also caused significant change in the growth rate of leaf area. Both higher fertilization and host density caused higher density of gallers. Total leaf area was positively associated with galler density, but within galled replicates, the galled leaves were larger than the ungalled leaves. Although highest levels of fertilization and density of host trees caused significant change in the densities of parasitoids, the rate of parasitism did not change. However, tree-density manipulations increased the rate of inquilinism, but on a very low level. Our results demonstrate a trophic cascade in the tropical galler and its parasitoids as a response to bottom-up effects.
Keywords: Plant quality; Plant vigour; Resource concentration; Trophic cascade; Tropical gallers